Welding of Low Alloy Steel DIN 15Mo3 by MIG/MAG Spot - عبود د.عدنان نعمة; عبد الصاحب نبيل كاظم; طعمة عامر عبد الله (Al-Khwarizmi Engineering Journal, 2017)
This research deals with the effects of welding variables using MIG/MAG spot by using Argon (Ar) gas and CO2 to show their effect on the mechanical characteristics and microstructure of low alloy steel type DIN15Mo3 and determine the optimum condition for the process of welding ; current & time. The results show the possibility of using CO2 and also Ar in low alloy steel welding with a little decrease in the shear force of not more than 13% for 4mm thickness and time 2sec. The shear force increased when using Ar instead of CO2 to be , The shear force reach 36KN when using Ar at 2mm thickness time of 8 sec and current of 220 Amp. , when used CO2 instead of Ar decreased shear force to 31KN reach decrease rate 13% while for a thikness of 4mm , time 8sec and acurrent of 290Amp. it was 37.9kN , when used CO2 became 30.9KN decrease rate 18.5% and for a thikness of 6mm , time 8 sec and 450Amp. current it was 39 KN when used CO2 it become 37KN redusing rate 5.20% .The diameter and penetration of welding have straight relation with the increase of current and time.